Urbanización y medioambiente: claves para el debate desde América Latina - Dammert-Guardia, Manuel; Vilela, Marta (Pontificia Universidad Católica del Perú, 2025)
In a global context of generalized urbanization, Latin America is characterized by its high rate of urban population, persistent inequality, and vulnerability to climate change. This article offers a panoramic introduction to the relationship between urbanization and environment, emphasizing the importance of expanding and giving greater attention to this agenda within urban studies. The topics discussed do not exhaust the field, but rather suggest possible research pathways. Moreover, the text helps situate the studies included in this issue of the journal.

En un contexto global de urbanización generalizada, América Latina se caracteriza por la alta tasa de población urbana, la desigualdad persistente y por su vulnerabilidad a los cambios climáticos. En este artículo ofrecemos una introducción panorámica sobre la relación urbanización y medioambiente, subrayando la importancia de que los estudios urbanos amplíen y otorguen mayor atención a esta agenda. Los temas señalados no agotan el campo de estudios, pero ofrecen posibles rutas de investigación. Además, el texto permite situar las investigaciones incluidas en este dossier de la revista.
Urbanization and Environment: Key Insights for Debates from Latin America
Keywords: Urbanization; Environment; Climate change; Latin America; Urbanización; Medioambiente; Cambio climático; América Latina; https://purl.org/pe-repo/ocde/ford#2.07.01